2022
DOI: 10.1186/s12864-022-08536-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparative transcriptome analysis provides insights into the molecular mechanisms of high-frequency hearing differences between the sexes of Odorrana tormota

Abstract: Background Acoustic communication is important for the survival and reproduction of anurans and masking background noise is a critical factor for their effective acoustic communication. Males of the concave-eared frog (Odorrana tormota) have evolved an ultrasonic communication capacity to avoid masking by the widespread background noise of local fast-flowing streams, whereas females exhibit no ultrasonic sensitivity. However, the molecular mechanisms underlying the high-frequency hearing differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 103 publications
0
2
0
Order By: Relevance
“…Supersonic hearing has been proposed as an adaption phenotype to background noises in their environments. Differential transcription in genes involved in neurogenesis and sensory perception has been proposed as one of the mechanisms underlying the evolution of this trait [148]. Multiple genes observed to be differentially transcribed in male and female anglerfish are involved in gene regulation or have roles within cellular pathways [148].…”
Section: Reproductive Adaptationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Supersonic hearing has been proposed as an adaption phenotype to background noises in their environments. Differential transcription in genes involved in neurogenesis and sensory perception has been proposed as one of the mechanisms underlying the evolution of this trait [148]. Multiple genes observed to be differentially transcribed in male and female anglerfish are involved in gene regulation or have roles within cellular pathways [148].…”
Section: Reproductive Adaptationsmentioning
confidence: 99%
“…Differential transcription in genes involved in neurogenesis and sensory perception has been proposed as one of the mechanisms underlying the evolution of this trait [148]. Multiple genes observed to be differentially transcribed in male and female anglerfish are involved in gene regulation or have roles within cellular pathways [148]. Thus, gene duplication, neofunctionalization, differential transcription, and gene losses have been important molecular mechanisms in reproductive adaptations.…”
Section: Reproductive Adaptationsmentioning
confidence: 99%
“…Several recent studies have been performed to assess the relative roles of DGE and AS in sexual differences and their results suggested that DGE and AS might function independently to mediate sexual differences [39,40]. However, few studies have been performed to explore the molecular mechanisms underlying the sexual differences of vocalizations and acoustic signals (but see [41]) and none have been conducted for the differences in echolocation pulse frequencies between males and females in bats.…”
Section: Introductionmentioning
confidence: 99%
“…To test for our proposal, we obtained mRNA-seq data of brain and liver from four individuals of each sex. Brain is responsible for regulation of almost all life activities and was recently used to study acoustic differences between the sexes of frog ( Chen et al, 2022 ). Liver is the primary organ for metabolism and is related to feeding.…”
Section: Introductionmentioning
confidence: 99%